Autonomia do enfermeiro no contexto hospitalar: uma análise foucaultiana - Soares, Sabrina Gonçalves Aguiar (2019)
The subject is constituted by relations of power, of normatividades and assujeitamento, which causes the subjectivity is produced on the relationship of forces that the cross. The hospital is marked by power relations that reflect on the power of decision and on the autonomy of the subjects nurses doing with that many, now present themselves as subjects of his work, now imprisoned by the dynamics of the hospital organization. Thus, it is defended as a thesis of this study, it is possible to check, at the same time, nurses who work in the hospital area, the weakening of the traditional image of the authority with the correlative strengthening of spaces of resistance, which produce the practice itself, subjectivities that are autonomous. The study followed the qualitative method, analytical, with theoretical methodological framework guided the discussion of the Hermeneutics of the subject in Foucault. Are Objectives: To know how is becoming the autonomy in the nurses' professional practice; and to analyze how the subject nurse designs in the discourse about the exercise of their autonomy in the hospital context. Comprised the empirical material of the study, articles published in Revista Brasileira de Enfermagem, between the years of 1986 to 2016, and narrative interviews, recorded on audio, with 18 nurses working in hospitalization units of medical and surgical clinic I and II, a public hospital in the Southern region of Brazil. The production of data occurred between the months of April to May 2018. The analysis made by the theoretical discourse analysis of Foucault's inspiration. The findings of this study allowed the organization of results in two chapters. The first chapter titled "Between the said and not said about the autonomy of the nurse: (des) continuities in speeches", revealed that the autonomy in the nurses' professional practice permeates the centrality of knowledge, by the political positioning and working conditions. Therefore, these factors reveal themselves as power devices in the construction of the governability of the nurse, allowing it to position yourself as a subject critical and reflective in the execution of their activities, in order to weaken the traditional image of authority of health institutions. The second, titled "Autonomy in professional exercise: Government itself of the nurse who works in the hospital area", revealed that the discourse of the subject nurse in the hospital context, referring to professional autonomy, permeates through a plurality of practices of self, which produce truths that subjetivam and govern the mode of being of the nurse directing it, either as a subject submissive, sometimes as a critical subject. Based on the results, it was concluded that although there is a regularity of practice of the nurse, outlined by discourses that underpin medical knowledge, it is possible to perceive a shy movement toward the discursive practices that refer to conditions of possibility of nurses become autonomous subject.